PENERAPAN MODEL AUDITORY INTELLECTUALLY REPETITION (AIR) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI F1 SMAN 2 BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Fajri, Fajri; Mardiah, Ainil; Edriati, Sofia (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research is motivated by the low level of student mathematics learning outcomes. The aim of this research is to find out whether there is an increase in the learning outcomes of class XI F1 students at SMAN 2 Basa Ampek Balai Tapan after implementing the Auditory Intellectually Repetition (AIR) model. This type of research is pre-experimental, with the research design used: one-group pretest and posttest design. The subjects in this research were class XI F1. The sampling technique in this research was purposive sampling, chosen as the sample class was class XI F1. The research instrument for this research was the initial pretest and posttest. Analysis of the learning outcomes data used was the paired t-test. The analysis of learning outcomes data, it was obtained =19,72 at the real level ?=0.05 with =1.729. Because the data produces then rejecting H0 means that student learning outcomes after applying the Auditory Intellectually Repetition model increase. Thus, there is an increase in the learning outcomes of class XI F1 students at SMAN 2 Basa Ampek Balai Tapan after implementing the Auditory Intellectually Repetition (AIR) model.